Chemical composition and energetic values of some feedstuffs for poultry - Albino, Luiz Fernando Teixeira; Fialho, Elias Tadeu; Rosa, Paulo Sérgio (Pesquisa Agropecuaria Brasileira, 2014)
Proximal chemical composition, minerals, aminoacid and crude energy analysis and metabolizable energy (ME), corrected metabolizable energy (MEn), apparent metabolizable dry matter (AMDM) and apparently metabolizable tryptophane coefficent (ATMC) of 16 feedstuffs utilized for poultry diets in Brazil were determined in a biological experiment. The experimental design was completely randomized with a 17 x 2 factorial arrangement (16 feedstuffs, and basal diets and two ages), three replications and ten birds in each experimental unit. Variations were found between chemical composition and energetic values in the feedstuffs analyzed and those found in the tables of foreign authors. There were no statistical differences (P>0.05) in the values of MEn, AMDM and ATMC for the feedstuffs utilized in broiler ration at the tested ages. The average values expressed on a dry matter basis for CME (kcal/g) and AMDM (%) obtained with broilers of two ages were 21 and 42 days, respectively: alfalfa hay: 2.67 and 56.64; peanut meal: 2.38 and 49.84; cowpea: 3.36 and 64; toasted cowpea: 2.93 and 57.07; cooked cowpea: 3.52 and 70.07; pigeon pea: 2.43 and 51.56; toasted pigeon pea; 2.49 and 46.66; cooked pigeon pea: 2.83 and 61.41; soybean meal: 3.14 and 6.20; swine meat and bone meal: 3.23 and 57.25; blood meal: 3.08 and 64.37; unfatted rice bran: 2.59 and 52.89; ground corn: 4.10 and 82.92; ground com 1: 3.78 and 85.56; ground com 2: 3.89 and 88,81; and wheat bran: 3.10 and 62.11.